Whole genome sequence analysis of Mycobacterium suricattae. Issue 6 (December 2015) - Dippenaar, Anzaan; Parsons, Sven David Charles; Sampson, Samantha Leigh; van der Merwe, Ruben Gerhard; Drewe, Julian Ashley; Abdallah, Abdallah Musa; Siame, Kabengele Keith; Gey van Pittius, Nicolaas Claudius; van Helden, Paul David; Pain, Arnab; Warren, Robin Mark
Summary: Tuberculosis occurs in various mammalian hosts and is caused by a range of different lineages of the Mycobacterium tuberculosis complex (MTBC). A recently described member, Mycobacterium suricattae, causes tuberculosis in meerkats ( Suricata suricatta ) in Southern Africa and preliminary genetic analysis showed this organism to be closely related to an MTBC pathogen of rock hyraxes ( Procavia capensis ), the dassie bacillus. Here we make use of whole genome sequencing to describe the evolution of the genome of M. suricattae, including known and novel regions of difference, SNPs and IS 6110 insertion sites. We used genome-wide phylogenetic analysis to show that M. suricattae clusters with the chimpanzee bacillus, previously isolated from a chimpanzee ( Pan troglodytes ) in West Africa. We propose an evolutionary scenario for the Mycobacterium africanum lineage 6 complex, showing the evolutionary relationship of M. africanum and chimpanzee bacillus, and the closely related members M. suricattae, dassie bacillus and Mycobacterium mungi .